2018
DOI: 10.1111/gcb.14081
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among plants, bacteria, and fungi reduce extracellular enzyme activities under long‐term N fertilization

Abstract: Atmospheric nitrogen (N) deposition has enhanced soil carbon (C) stocks in temperate forests. Most research has posited that these soil C gains are driven primarily by shifts in fungal community composition with elevated N leading to declines in lignin degrading Basidiomycetes. Recent research, however, suggests that plants and soil microbes are dynamically intertwined, whereby plants send C subsidies to rhizosphere microbes to enhance enzyme production and the mobilization of N. Thus, under elevated N, trees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 88 publications
(152 reference statements)
5
120
5
1
Order By: Relevance
“…Emerging research suggests that soil enzyme activities decline in response to long-term N fertilization in forest ecosystems due to a cascade of ecosystem responses affecting both microbial community composition and plant C allocation belowground (54). However, soil enzyme activities did not change in response to the N addition in this SDTF, probably because the short-term N fertilization was not enough to induce significant shifts in the microbial community and plant C allocation in these tropical soils, which seem not to be limited by N availability.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging research suggests that soil enzyme activities decline in response to long-term N fertilization in forest ecosystems due to a cascade of ecosystem responses affecting both microbial community composition and plant C allocation belowground (54). However, soil enzyme activities did not change in response to the N addition in this SDTF, probably because the short-term N fertilization was not enough to induce significant shifts in the microbial community and plant C allocation in these tropical soils, which seem not to be limited by N availability.…”
Section: Discussionmentioning
confidence: 99%
“…Saleem et al (2018) suggested that root system architecture altered the root microbiome structure. Marschner and Timonen (2005) demonstrated that an interaction between plant species and mycorrhizal colonization affected soil bacterial community structure in the rhizosphere. Also, soil type, nutrition, fertilization and root zone location would influence soil bacterial diversity (Marschner et al, 2001(Marschner et al, , 2004Berg and Smalla, 2009).…”
Section: Influence Of Distance To Roots On Soil Properties and Bactermentioning
confidence: 99%
“…We speculate that N application may change the requirement of soil microbes on C, N, and P, as well as affect soil organic matter (SOM) decomposition. However, the effect of N addition on soil microbial biomass has been found to be inconsistent; some studies found that N addition decreased soil microbial biomass [49,50]; recent research found that N addition first increased and then decreased the soil microbial PLFA content in a study conducted on the Loess Plateau [39]. Enhanced N deposition reduced soil microbial biomass and biomass respiratory efficiency in an oak forest [8].…”
Section: Response Of Soil Microbial Biomass To N Applicationmentioning
confidence: 99%